Social Policy: From the Death of Welfare State to the State “Nameless”. An historic overview of Social Policies in South and Eastern Countries - Santos, Clara Cruz (Socialinė teorija, empirija, politika ir praktika, 2017)
Social policies play an important role in social systems organisation and in the definition of Social Work strategy within the public life. Understanding the diverse rationalities that embody State and Governments rhetoric and real action is the main goal of this article, highly centred in Social Policies and their paradoxical procedures in social and personal well being. We argue that in most South and Eastern Countries coexists a different form of governance and of public responses to the social needs which led to a difficulty in understanding actual ideology that defines social policies measures and intends. This analysis can’t be done disentailed of an analysis how the different political forms of State have influenced the features and the goals of social policies understood as a sector of public policy.